65. studentská vědecká konference Program a sborník abstraktů - Jurajda, Michal (Masaryk University Press, 2021)
Title in English: The 65th Student Scientific Conference. The publication contains overview of lectures that were presented at the 65th Student Scientific Conference, organised by the Faculty of Medicine, MU on 9 November 2021.